A Critical Review of “Economic Development” - Seyed Hossein Mirjalili (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This book deals with the analysis of developing economies in Asia, Africa, Latin America, and Eastern and Central Europe which comprises about 85% of the world's population. The text is problematic and addresses the issues of developing countries in the form of a question in nineteen chapters and has responded to them. The content of the work covers most of the topics in economic development syllabus. Logical order and internal consistency exist in different sections and chapters of the book. This work is compared with the economic development by Todaro and its advantages are discussed. The report of the Commission on Growth and Development, Growth Diagnostics, Behavioral Development Economics, the method of analytic narratives and the method of controlled experiment are new issues of economic development that have not been discussed in this text.  The method of evaluation is analytical-comparative through which the content of the text is compared to a well-known text for neglecting new topics discussed in the new texts of economic development.